2020
DOI: 10.1101/2020.11.18.20234468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of COVID-19 vaccine acceptance among healthcare workers in Los Angeles

Abstract: ImportanceHealthcare workers (HCW) are slated to be early recipients of SARS-CoV-2 vaccines due to increased risk of exposure to patients with COVID-19, and will be tasked with administering approved vaccines to the general population. As lynchpins of the vaccination effort, HCWs’ opinions of a vaccine’s safety and efficacy may affect both public perception and uptake of the vaccine. Therefore, it is crucial to understand and address potential hesitancy prior to vaccine administration.ObjectiveTo understand he… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
87
5
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 23 publications
(32 reference statements)
12
87
5
8
Order By: Relevance
“…Hesitancy to get vaccinated was reported to be associated with younger age, female gender, lower income, lower level of education and black ethnicity [ 21 , 23 , 24 , 30 32 ]. In line with previous reports [ 21 , 23 , 24 , 30 34 ], we observed that working in a hospital especially being a physician, being male, being older than 40 years of age, not having contracted COVID-19 and having higher scores on CAS were found to be independently associated with vaccine acceptance. Females were more reluctant to get vaccinated as they tend to inquire more about health-related information (which can mean increased exposure also to misinformation) and they make the majority of health care decisions for their children and other family members [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hesitancy to get vaccinated was reported to be associated with younger age, female gender, lower income, lower level of education and black ethnicity [ 21 , 23 , 24 , 30 32 ]. In line with previous reports [ 21 , 23 , 24 , 30 34 ], we observed that working in a hospital especially being a physician, being male, being older than 40 years of age, not having contracted COVID-19 and having higher scores on CAS were found to be independently associated with vaccine acceptance. Females were more reluctant to get vaccinated as they tend to inquire more about health-related information (which can mean increased exposure also to misinformation) and they make the majority of health care decisions for their children and other family members [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with previous studies done among the hospital workers [ 33 ]. In a recent study, nurses were found to be more likely to delay the vaccination compared to physicians [ 34 ]. In another, nearly half or more of nurses and various types of medical personnel were not sure whether the vaccine will work and protect them against COVID-19 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As also shown in studies from France, Congo, and Israel [ 12 , 20 , 23 ], physicians were more likely to report intention to get vaccinated against COVID-19 compared to other professions. In particular in our survey 71.5% of physicians and 43% of nursing personnel favored COVID-19 vaccination, which is similar to the 40% acceptance rate reported among nurses in Hong-Kong and the significant intention rate to delay COVID-19 vaccination among nurses compared to physicians in a Los Angeles study [ 11 , 24 ]. As of March 17 2021, the nationwide COVID-19 vaccine uptake rates were 77% among physicians and 51% among nursing personnel, which are increased compared to the recorded rates of intention to get vaccinated in our survey.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, in the multi-country study of Verger et al [15], which also assessed health care vaccine among health care workers in this study was lower than that reported in Saudi Arabia [25], China [26,27], France [18], and the United States [13,20,28]. For instance, Shaw et al Research has shown that health care workers intending to be vaccinated plan to recommend the vaccine to family and friends [19].…”
Section: Discussionmentioning
confidence: 60%